2018
DOI: 10.1016/j.juro.2018.03.132
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistency in the Definition of Urinary Tract Infection after Intravesical Botulinum Toxin A Injection: A Systematic Review

Abstract: Definitions of urinary tract infection are heterogeneous and frequently absent in the literature on onabotulinumtoxinA to treat overactive bladder and/or neurogenic bladder. Given the potential for post-procedure urinary symptoms in this setting, explicit criteria are imperative to establish the true urinary tract infection rate following treatment with onabotulinumtoxinA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The controversy regarding UTI definitions was also described in a systematic review trying to more accurately examine the UTI rate following botulinum injections; they found that amongst 50 selected publications, only 27 had defined the UTI with a total of 10 different definitions [43]. Two studies used the National Institute on Disability and Rehabilitation Research [44] UTI definition, whereas no studies used a definition which met the European Association of Urology [4] or Infectious Diseases Society of America [41] criteria.…”
Section: Uti: Definitions Diagnoses and Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The controversy regarding UTI definitions was also described in a systematic review trying to more accurately examine the UTI rate following botulinum injections; they found that amongst 50 selected publications, only 27 had defined the UTI with a total of 10 different definitions [43]. Two studies used the National Institute on Disability and Rehabilitation Research [44] UTI definition, whereas no studies used a definition which met the European Association of Urology [4] or Infectious Diseases Society of America [41] criteria.…”
Section: Uti: Definitions Diagnoses and Perceptionsmentioning
confidence: 99%
“…Detrusor treatment with Botulinum Toxin A injections efficiently combats neurogenic detrusor overactivity [70] but there is controversy about the UTI rates postinjection [43] and whether there should be antibiotic coverage for the therapeutic sessions [71]. Data from a single SCI rehabilitation centre, comprising 1104 patients with at least 3 years follow-up, found that the odds of a UTI increased 10-fold for those receiving botulinum detrusor injections [6].…”
Section: The Model: Local Urinary Tract Conditionsmentioning
confidence: 99%
“…We also followed the European Association of Urology guidelines for UTI diagnostic criteria in the subanalysis since UTI definitions have been inconsistent among studies. 16 Another group assessing men and women undergoing their first intravesical BTX-A injection for refractory idiopathic detrusor overactivity found that women were more likely to have a UTI after injection . 17 However, as women are at higher risk for UTI at baseline, it is unclear whether recent UTIs (prior to injection) played an additional role in their study.…”
Section: Discussionmentioning
confidence: 99%
“…8 The incidence of bacteriuria after cystoscopic intravesical injection of BoNT-A is high 9 and there is debate as to what constitutes symptomatic urinary tract infection (UTI) following intravesical injection of BoNT-A. 10 The rate of postoperative UTI is accepted to be about 15%. 11 Perioperative antibiotic prophylaxis is therefore recommended to reduce the risk of postoperative UTI.…”
Section: Introductionmentioning
confidence: 99%